Effects of site elevation and grazing exclusion on phenolic compound production in Nardus stricta plants in high-elevation grasslands - Jorge Durán; Xoaquín Moreira; Marta Correia; Ana Cao; Joana Serôdio; Susana Rodríguez-Echeverría; Alexandra Rodríguez (PLoS ONE, 2025)
Specialized plant metabolism, particularly phenolic compound production, contributes significantly to the functioning and resilience of mountain ecosystems. Livestock grazing can influence phenolic production, with its effects varying depending on microclimatic factors and soil conditions. Despite the ecological significance of this process, the impact of livestock grazing on phenolic production in alpine plants remains insufficiently explored. To address this knowledge gap, we conducted a field experiment to investigate the individual and combined effects of site elevation and experimental grazing exclusion on phenolic compound production in Nardus stricta plants. After two growing seasons, we collected leaf samples to quantify phenolic diversity and concentration. Site elevation significantly affected phenolic richness and flavonoid concentrations, with higher levels at the highest elevation compared to lower sites. However, livestock grazing exclusion had no significant impact on phenolic concentration, diversity, or any interactions between grazing exclusion and site elevation across sites. This study enhances understanding of plant chemistry and responses to stressors, offering insights into plant adaptations to environmental and land-use changes.